Modification of Jordanian Zeolitic Tuff Using Cationic Surfactants and Their Capacity for Phenols Removal - A. Bazbaz, Ibrahim; I. Yousef, Rushdi; M. Musleh, Salem (Asian Journal of Chemistry, 2011)
Zeolites have large cation exchange capacities, which enable them to be modified by cationic surfactants. Native zeolitic tuff was treated with different cationic surfactants, viz., dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, and octadecyltrimethylammonium bromide. The unmodified as well as the surfactant modified zeolites were characterized by powder X-ray diffraction, X-ray fluorescence, and infrared spectroscopy techniques. The chain length of the surfactant plays a significant role in determining the amount of surfactant loaded on zeolite surface. The total organic carbon analyses of surfactant modified zeolites revealed that hexadecyltrimethylammonium bromide has the highest affinity to be adsorbed on zeolite surface, whereas the octadecyltrimethylammonium bromide has the lowest affinity due to the possible hydrocarbon chain coiling. The surfactant modified zeolite samples were employed to study the influence of the different surfactants on the uptake of phenol, 4-chlorophenol and 4-nitrophrnol onto the zeolitic tuff. It was found that there is a correlation between the chain length of the surfactant tail and the uptake of phenols on zeolite. However, the uptake of phenols at pH 9.3 was found to follow the order 4-nitrophenol > 4-chlorophenol > phenol.